2021
DOI: 10.1038/s41467-021-26685-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary metabolic landscape from preneoplasia to invasive lung adenocarcinoma

Abstract: Metabolic reprogramming evolves during cancer initiation and progression. However, thorough understanding of metabolic evolution from preneoplasia to lung adenocarcinoma (LUAD) is still limited. Here, we perform large-scale targeted metabolomics on resected lesions and plasma obtained from invasive LUAD and its precursors, and decipher the metabolic trajectories from atypical adenomatous hyperplasia (AAH) to adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 66 publications
6
67
0
Order By: Relevance
“…We showed that the metabolism pathway was shared by ACSL5 , FUT2 , and SERINC2 . A recent study [ 37 ] has reported that the metabolic pathways emerge in premalignant lesions and that metabolite-based clustering showed different survival outcomes, possibly facilitating early detection of high-risk cancers. Our results revealed the candidate genes linked to the evidence that metabolic pathways emerge in premalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the metabolism pathway was shared by ACSL5 , FUT2 , and SERINC2 . A recent study [ 37 ] has reported that the metabolic pathways emerge in premalignant lesions and that metabolite-based clustering showed different survival outcomes, possibly facilitating early detection of high-risk cancers. Our results revealed the candidate genes linked to the evidence that metabolic pathways emerge in premalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic changes are not homogeneous in tumors; there are differences between types of cancer originating in different tissues and within the same tissue, such as breast cancer, where metabolic alterations have different nuances depending on the intrinsic subtype of breast cancer and the degree of differentiation [ 300 ]. Additionally, in vivo studies reveal the metabolic heterogeneity of cancer throughout tumor progression [ 11 , 301 ], whereby they are more dependent on OXPHOS metabolism in more advanced stages [ 91 ]. Indeed, OXPHOS inhibitors have been proposed for use in treating cancer and are undergoing clinical trials at the time of writing [ 302 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analysis displayed significant upregulation of bile acid metabolism, K-RAS signal, and fatty acid metabolism in high-IRS groups. Previous studies already showed that bile acid metabolism and fatty acid metabolism contributed to the tumor invasion (24,25). Oncogenic K-RAS signaling that has been studied extensively promotes tumor progression in several cancers.…”
Section: Discussionmentioning
confidence: 99%